Analysis of Criminal Sanctions on Perpetrators of Online Buying and Selling Fraud - Bella Monica Rahma Hamida; Normalita Destyarini (Justisia: Jurnal Ilmu Hukum, 2023)
Online buying and selling fraud, commonly referred to as e-commerce fraud, is a prevalent criminal activity that involves deceiving individuals for financial gain through fraudulent online transactions. This form of fraud encompasses various practices, including non-delivery of goods, sale of counterfeit products, identity theft, and phishing schemes. To combat this issue, legal systems impose criminal sanctions on individuals involved in online buying and selling fraud. The analysis of these criminal sanctions reveals that they aim to deter and punish perpetrators while providing restitution to victims. The specific nature and severity of sanctions differ across jurisdictions, as they are influenced by the legal framework, cybercrime legislation, and consumer protection laws of each country. Understanding the range of criminal sanctions is crucial in developing effective measures to prevent and address online buying and selling fraud in a globalized digital landscape. In this era of technological advancement, people prefer to buy things online. But with the development of technology, the idea of crime by unscrupulous actors has also developed. One example is the criminal act of fraud. Fraud is a condition carried out by anyone with the intention of benefiting them selves or others unlawfully. Then the method used to conduct this research is the normative method. The type of data used in this research is secondary data. This secondary data is obtained by researchers from other research results, journals, books, and other sources that are collected and compiled so that they can solve cases.